ECOGEOGRAPHICAL AND GERMPLASM CHARACTERIZATION OF JATROPHA CURCAS LINNAEUS (L.) IN JIGAWA STATE: IMPLICATIONS FOR BIOFUEL PRODUCTION - Abubakar A, Wada; Abdulazeez; Abdurrahman Y., Sadiq; Salami K., Dele; Bello Z., Titilope; Daudu O. A., Yusuf (FUDMA Journal of Sciences, 2025)
Jatropha curcas L. is a multipurpose plant species with significant potential for biofuel production, soil conservation, and livelihood improvement. Despite its importance, there is a dearth of information on the ecogeographical distribution, genetic diversity, and germplasm characteristics of J. curcas in Jigawa State, Nigeria. This study aims to conduct an ecogeographical and germplasm characterization of J. curcas in Jigawa State, with a view to informing and enhancing biofuel production, conservation, and sustainable utilization of this species. This study presents an ecogeographical and germplasm characterization of Jatropha curcas L. in Jigawa State, Nigeria, with implications for biofuel production, conservation, and sustainable utilization. Five accessions were collected from Hadejia, Kazaure, Gumel, Birnin Kudu, and Miga, representing diverse ecological conditions. Ecogeographical data (latitude, longitude, soil type, climate characteristics) and morphological traits (plant height, stem diameter, leaf dimensions, fruit yield, oil content) were recorded. Analysis using descriptive statistics, ANOVA, correlation matrix, PCA, and cluster analysis revealed variability in growth performance and genetic diversity across accessions. The study provides insights into J. curcas’ adaptability, yield potential, and genetic diversity, informing strategies for biofuel production, conservation, and sustainable utilization in Jigawa State, Nigeria.